Faktor yang mempengaruhi tekanan kerja dalam kalangan pegawai perubatan di Wad Psikiatri Hospital Permai, Johor Bahru - Hamadi, Othman (2020)
Stress refers to the formation of behavior and the impact on one's emotions. The study was conducted to identify factors that influence work stress among Assistant Medical Officers at the Permai Hospital Psychiatric Ward, Johor Bahru. This study aimed to look at the differences in work pressure factors based on demographics (age, duration of service and marital status). Futhermore, there are six stress factors studied namely work and work barriers, organizational structure and climate, management roles, careers and achievements, workplace relationships and work instructional factors. The instrument used for this study was the Occupational Stress Indicator (OSI). A total of 80 staff were selected as respondents to represent the population. The data obtained were analyzed using Statistical Package for The Social Science (SPSS) version 25. The study used quantitative methods as it is useful for obtaining extensive information on factors influencing work pressure based on demographic data in the short run. The results show that a significant relationship between the factor of work pressure and the level of work stress exists.